PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MELALUI METODE COOPERATIVE LEARNING TEKNIK GRUP INVESTIGASI - Khaeriyah, Finny (Pascasarjna Universitas Negeri Jakarta, 2016)
Abstract: This study aimed to describe the process and learning outcomes of social science through cooperative methods with techniques Group Investigation. The research model used is a model Kemmis and Taggart to the study subjects were 27 students of State Elementary School. The study was conducted from January 2016 to March 2016. The study was conducted over 6 meeting is divided into three cycles. Data collected through the test data and non-test. Data analysis techniques used in this research is the analysis of qualitative data. Qualitative analysis is used to explain the study results. The results showed an increase in student learning outcomes in children after learning followed by using the method of investigation group. pre-cycle, the first, and cycle increased as a result of studying social science achievement of students in the second cycle is also not meet the criteria of success of the action then followed the third cycle increased to 81.38 %. The results showed an increase learning outcomes of social science in grade 3 elementary school conducted through cooperative methods with techniques Group Investigation. Keywords: learning outcomes of social studies, engineering Group Investigation, research actionsAbstrak: Penelitian ini bertujuan untuk menggambarkan proses dan hasil belajar ilmu pengetahuan sosial melalui metode kooperatif dengan teknik Group Investigation. Model penelitian yang digunakan adalah model Kemmis dan Taggart dengan subyek penelitian adalah 27 siswa kelas 3 Sekolah Dasar. Penelitian ini dilakukan dari Januari 2016 sampai Maret 2016. Penelitian ini dilakukan selama 6 pertemuan yang terbagi dalam tiga siklus. Teknik pengumpulan data dilakukan melalui data tes dan non tes. Teknik analisis data yang digunakan dalam penelitian ini adalah analisis data kualitatif . Analisis kualitatif digunakan untuk menjelaskan hasil penelitian. Hasil penelitian menunjukkan peningkatan hasil belajar siswa pada anak-anak setelah pembelajaran diikuti dengan menggunakan metode grup investigasi. Pada pra siklus, siklus I dan II mengalami peningkatan. Hasil penelitian menunjukkan adanya peningkatan hasil belajar ilmu pengetahuan sosial pada siswa kelas 3 sekolah dasar yang dilakukan melalui metode kooperatif dengan teknik Group Investigation.Kata kunci: hasil belajar ilmu pengetahuan sosial, teknik Group Investigation, penelitian tindakan